2022
DOI: 10.3389/fonc.2022.991724
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Treatment of metastatic dedifferentiated chondrosarcoma with pembrolizumab yields sustained complete response

Abstract: Dedifferentiated chondrosarcomas (DDCS) are aggressive tumors with poor outcomes. Treatment of localized DDCS is primarily surgical, though most patients present with unresectable or metastatic disease. Systemic treatment options for advanced DDCS are limited, and the benefits of chemotherapy in this patient population remain controversial. Among other systemic therapy options, there is emerging clinical evidence to support the use of immunotherapy in patients with advanced DDCS. However, studies regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Increasing clinical evidence indicates that immunotherapy might be effective against advanced DDCS [73][74][75][76][77]. Kostine et al analyzed DDCS tissues, showing the expression of programmed cell death 1-ligand 1 (PD-L1) in 52% of samples and large T-cell infiltration [73].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing clinical evidence indicates that immunotherapy might be effective against advanced DDCS [73][74][75][76][77]. Kostine et al analyzed DDCS tissues, showing the expression of programmed cell death 1-ligand 1 (PD-L1) in 52% of samples and large T-cell infiltration [73].…”
Section: Discussionmentioning
confidence: 99%
“…In a case report study by Singh et al, which examined the effect of immunotherapy on PD-L1-positive DDCS, pembrolizumab (200 mg every 3 weeks) was administered after palliative resection. The patient showed a remarkable response with regression of metastatic foci and a complete sustained response for 24 months [58]. Among 22 whole-tissue samples of DDCS analysed by Kostine et.…”
Section: Immunotherapymentioning
confidence: 94%
“…Several studies have shown that DDCS tumours are often infiltrated by various immune cells, including macrophages and lymphocytes [7,29,[56][57][58]. Malchenko et al study of lung metastases in DDCS observed the presence of leukocyte infiltration in these metastases, which may have been involved in the metastatic spread in DDCS.…”
Section: Cellular Infiltratesmentioning
confidence: 98%
See 1 more Smart Citation
“…After ten months, the patient reported the presence of an unchanged 4 mm pulmonary nodule and no metastatic disease in the abdomen and pelvis. Surprisingly, although after 29 cycles he discontinued the pembrolizumab treatment due to immunotherapy-induced psoriatic arthritis, the patient continued to have a complete response on surveillance imaging [ 122 ].…”
Section: Immunotherapymentioning
confidence: 99%